TERT Promoter Mutations Are Enriched in Oral Cavity Cancers and Associated With Locoregional Recurrence. (2021) - Yu, Yao; Fan, Dan; Song, Xinmao; Zakeri, Kaveh; Chen, Linda; Kang, Jung; McBride, Sean; Tsai, C. Jillian; Dunn, Lara; Sherman, Eric; Katabi, Nora; Dogan, Snjezana; et al.
Abstract : PURPOSE: Telomerase reverse transcriptase ( TERT ) promoter mutations are prognostic in many cancers and have been observed in human papillomavirus (HPV)–negative head and neck squamous cell carcinomas (HNSCCs). However, the role of TERT promoter mutations in HPV-negative HNSCCs remains poorly understood in these cancers, which have increased risk for locoregional failure (LRF). PATIENTS AND METHODS: We retrospectively identified patients who were diagnosed with HNSCC between July 1, 2004, and October 12, 2017, at Memorial Sloan Kettering Cancer Center and whose tumors underwent next-generation sequencing using the MSK-IMPACT panel. Patients with HPV-positive oropharyngeal squamous cell carcinoma (SCC) were excluded. Cumulative incidence of LRF, patterns of failure, and overall survival were measured. RESULTS: We identified 117 patients with SCC of the oral cavity (OSCC), larynx, hypopharynx, or HPV-negative oropharynx whose tumors underwent next-generation sequencing. Sequencing was performed on 95 tumors that were obtained after recurrence and 22 that were obtained before recurrence. TERT promoter mutations were enriched in OSCC compared with laryngopharyngeal cancers (81.1% v 7.0%; P < .001), which was the largest genetic difference between these anatomic disease subsites. TERT promoter mutations were associated with LRF in OSCCs (Gray's test, P < .001) and in the overall cohort (Gray's test, P < .001). On multivariate analysis, TERT promoter mutations were associated with an increased risk for LRF (subdistribution hazard ratio, 2.82; 95% CI, 1.47 to 5.42; P = .0019), independent of oral cavity primary site and TP53 mutation status. CONCLUSION: TERT promoter status is associated with the cumulative incidence of LRF and patterns of failure. TERT promoter mutations may define a subset of OSCCs with unique pathogenesis that is associated with an increased risk of LRF. Validation in prospective cohorts is warranted.